Emerging Trends in Library and Information Science Research (Journal of Social Sciences Review, 2025)
This article examines the ongoing Library and Information Science (LIS) research, whose dramatic transformations it notes as a function largely of technological advancement, ongoing evolution in user expectation, and an emphasis on equitable information access. Innovative technologies such as artificial intelligence (AI), big data analytics, and block chain are modernizing information management and library services as key areas of investigation. It also mentioned that there are user centered approaches to promote inclusivity and community engagement as well as ethical problems, including data privacy, algorithmic bias. The research also shows how libraries are vital to academic and professional research work, and how they must also disentangle themselves from social and ethical problems in the digital space. It also urges for a multidisciplinary perspective in LIS research, that is, to conduct collaboration with other fields for addressing the requirements of many different user communities. The ultimate goal is to foster future library practices that take advantage of the new opportunities presented, and professional landscape of LIS that ensures libraries are relevant and responsive to new societal needs.
Keywords: Emerging Trends; Library and Information Science Research; Artificial Intelligence